A Differential Game of Transboundary Pollution Control and Ecological Compensation in a River Basin. (12th February 2020) - Yi, Yongxi; Wei, Zhongjun; Fu, Chunyan
Abstract : This paper investigates a Stackelberg differential game between an upstream region and a downstream region for transboundary pollution control and ecological compensation (EC) in a river basin. Among them, the downstream region as the leader chooses its abatement investment level and an ecological compensation rate to encourage upstream investing in water pollution control firstly. After then, the upstream region as the follower determines its abatement investment level to maximize welfare. FFurthermore, we take into consideration the effects of efficiency-improving and cost-reducing learning by doing which are originated from abatement investment activity of both regions simultaneously. The results show the following. (i) There is an optimal ecological compensation rate and under which a Pareto improvement result can be obtained. (ii) Carrying out EC will shift some abatement investment from the downstream region into the upstream region. (iii) The efficiency-improving and cost-reducing learning by doing derived from abatement investment activity of both regions can decrease the optimal ecological compensation rate, increase abatement investment, and improve the social welfare.